2004
DOI: 10.1023/b:jmsm.0000046396.14073.92
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of the biocompatibility of various silicon nitride ceramic qualities in vitro

Abstract: There is a controversy about the biocompatibility of silicon nitride ceramics contained in the literature, which appears to be related to a factor of the individual chemical composition of different qualities of silicon nitride ceramics and of the different surface properties. This study attempts to investigate the cytotoxicity of different qualities of industrial silicon nitride ceramics applying an L929-cell culture model in a direct contact assay combined with a cell viability assessment. Five different qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 16 publications
7
86
0
2
Order By: Relevance
“…The in vitro cytotoxicity test is a standard test that provides information on the interactions between cells and the surface of the material, and is often used as an initial evaluation of biocompatibility [30][31][32]. Here, the viability of cells was evaluated after a 24 hour period, and no significant difference was found between the positive control and the capsules (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro cytotoxicity test is a standard test that provides information on the interactions between cells and the surface of the material, and is often used as an initial evaluation of biocompatibility [30][31][32]. Here, the viability of cells was evaluated after a 24 hour period, and no significant difference was found between the positive control and the capsules (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…SiNx is a prospective coating material for metal joint replacements [1][2][3][4][5] ; it is a biocompatible compound 6 with a comparatively high hardness as well as wear resistance. Potential SiNx wear debris dissolves slowly in aqueous solution [7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation compared industrial-grade silicon nitride using the L929-cell culture model, with alumina and titanium alloy as controls. 41 Again, silicon nitride ceramics showed no cytotoxicity and favorable physicochemical properties. Investigators concluded that silicon nitride ceramic should be considered for biomedical applications.…”
Section: Biocompatibility Of Silicon Nitridementioning
confidence: 99%